The Oxidation of Hydroxylamine on Gold Electrodes in Mildly Acidic Aqueous Electrolytes: Electrochemical and In Situ Differential Reflectance Studies - Chen, Youjiang; Martins de Godoi, Denis R. [UNESP]; Scherson, Daniel (Electrochemical Soc Inc, 2011)
The oxidation of hydroxylamine (HAM) on polycrystalline Au electrodes has been examined in aqueous acetate buffer (pH = 4) using electrochemical and in situ reflectance spectroscopic techniques. Cyclic voltammograms recorded under quiescent conditions in the potential region negative to the onset of Au oxidation were characterized by two clearly defined peaks centered at ca. 0.42 V and ca. 0.76 V versus SCE. Corresponding polarization curves obtained with a Au rotating disk electrode (RDE) as a function of rotation rate, omega, yielded two rather well defined plateaus. However, plots of the limiting currents, i(lim), versus root omega, and particularly of i(lim) versus the concentration of HAM at fixed omega, were found to be non-linear pointing to complexities in the reaction mechanism. Experiments involving dual electrode techniques, including rotating ring-disk electrodes, afforded evidence that the two sequential redox waves are associated primarily with the oxidation of HAM to nitrite and nitrate, respectively. Normal incidence differential reflectance spectroscopy measurements, Delta R/R, on a Au RDE performed either at high omega or large [HAM] failed to detect the presence of Au oxide during HAM oxidation in the potential region in which Au is known to undergo oxidation. This behavior is analogous with that found earlier in our laboratories for the oxidation of bisulfite on Au. (C) 2011 The Electrochemical Society. [DOI: 10.1149/1.3527986] All rights reserved.